EFFECT OF GROWTH REGULATING SUBSTANCES ON THE CHLOROPHYLL, NITRATE REDUCTASE, LEGHAEMOGLOBIN CONTENT AND YIELD IN GROUNDNUT (ARACHIS HYPOGAEA) - PUSHP SHARMA; VIRENDER SARDANA (The Bioscan, 2012)
Regulation of the plant metabolism by exogenous growth regulating substances offers new possibilities in circumventing environmental limitations, relaxing genetic restrains, improving the quality and aiding production. The effect of foliar application of growth regulating substances i.e. indole acetic acid (IAA)@5 and 7.5ppm followed by a second spray of Ethrel@25ppm, sequential spray of Mepiquat chloride @125ppm and Mepiquat chloride@125ppm+Ethrel@25ppm was studied in groundnut (Arachis hypogaea L) cultivars SG99 and M13 under field conditions. Chlorophyll content increased with the foliar application of IAA @5ppm+Ethrel 25ppm in both the cultivars. Chla, Chlb and total chlorophyll enhanced with the Mepiquat chloride @125ppm + Ethrel 25ppm in SG99. Nitrate reductase activity did not vary much in SG99 with foliar applications; however in cultivar M13, it increased in leaves with IAA@ 7.5ppm+ Ethrel 25ppm. Both the concentrations of IAA increased the nitrate reductase activity in the nodules of SG99. Leghaemoglobin content increased with IAA@ 5ppm+ Ethrel 25ppmin both the cultivars, whereas Mepiquat chloride @125ppm + Ethrel 25ppm was effective only in M13 as compared to control. Number of mature/developed pods, immature pods and gynophores increased with the foliar sprays. Sequential application of IAA@ 7.5ppm+ Ethrel 25ppm increased the pod yield of SG99 and M13 to the tune of 10 and 8 per cent respectively over control.